The Effect of Non-Native Accents and Stereotypes on Speaker Perception and Comprehension - Baghdasaryan, Susanna (Armenian Folia Anglistika, 2017)
The paper argues that linguistic forms per se do not have any positive or negative meaning and that one form is not better than the other. However, this is not fully perceived outside the narrow linguistic community. Very often it is demonstrated by the apparent stigmatization of non-native accents by native speakers of the language. This phenomenon seems true in reference to many communities and languages. Different sociolinguists have conducted research to prove the ungrounded nature of linguistic partiality. They try to account for the listeners’ attitudes towards non-native speech by incorporating the model of dual cognitive processing methods, namely implicit and explicit. They believe that attitudes are formed by the interaction of these two cognitive mechanisms. The negative attitude can be cured by application of more explicit cognitive techniques.
Keywords: native speakers; non-native accents; Sociolinguistics; cognitive mechanisms; partiality; implicit/explicit mechanisms; stigmatization